2021
DOI: 10.3233/jad-210145
|View full text |Cite
|
Sign up to set email alerts
|

Potential Novel Genes for Late-Onset Alzheimer’s Disease in East-Asian Descent Identified by APOE-Stratified Genome-Wide Association Study

Abstract: The present study reports two novel genome-wide significant loci for late-onset Alzheimer’s disease (LOAD) identified from APOE ε4 non-carrier subjects of East Asian origin. A genome-wide association study of Alzheimer’s disease was performed in 2,291 Korean seniors in the discovery phase, from the Gwangju Alzheimer’ and Related Dementias (GARD) cohort study. The study was replicated in a Japanese cohort of 1,956 subjects that suggested two novel susceptible SNPs in two genes: LRIG1 and CACNA1A. This study dem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 45 publications
0
20
1
Order By: Relevance
“…This is the first meta-analysis to establish a significant association between ALDH2 * 2 and LOAD in the Asian population. Although none of the recent genome wide association studies using Caucasian samples [ 46 ] or Asian samples [ 47, 48 ] detected genome-wide significance of the ALDH2 gene, this analysis suggested that ALDH2 * 2 has some role in the pathogenesis of LOAD in the Asian population. Interestingly, a recent genome-wide associated study in a Han Chinese population showed that ALDH2 * 2 was associated with serum uric acid by affecting alcohol consumption [ 49 ].…”
Section: Discussionmentioning
confidence: 69%
“…This is the first meta-analysis to establish a significant association between ALDH2 * 2 and LOAD in the Asian population. Although none of the recent genome wide association studies using Caucasian samples [ 46 ] or Asian samples [ 47, 48 ] detected genome-wide significance of the ALDH2 gene, this analysis suggested that ALDH2 * 2 has some role in the pathogenesis of LOAD in the Asian population. Interestingly, a recent genome-wide associated study in a Han Chinese population showed that ALDH2 * 2 was associated with serum uric acid by affecting alcohol consumption [ 49 ].…”
Section: Discussionmentioning
confidence: 69%
“…The GO term analyses of synergistically and non-synergistically expressed genes also verified these findings, as synergistic genes enriched pathways related to toxic protein response and glial cell differentiation pathways, while non-synergistic genes enriched the processes related to neurogenesis, neurotransmitter release, or RNA processing ( Figure 7 B). LRIG1 was recently identified in an AD GWAS of east Asian ancestry [ 101 ], and the gene encodes a transmembrane protein that controls the extent of the epidermal growth factor signaling by suppressing the EGF receptor (EGFR) availability [ 102 ]. EGF signaling is important for astroglial activation and priming for neurogenesis [ 50 ], and therefore upregulation of LRIG1 in human AD (logFC = 0.882, p = 0.0087) and downregulation in zebrafish (logFC = −0.353, p = 4.1 × 10 −6 ) can point towards a differential neurogenesis response in humans and zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Since the lead SNPs for these potential novel loci were absent in the East Asian dataset used for initial discovery 19 , we attempted to test these SNPs in an independent East Asian ancestry dataset 20 . We observed a nominally significant association at VWA5B2 -rs9837978 (P=0.048, β=0.204) in the GARD cohort (n=2,291), although the direction of effect was not consistent with the datasets included in the discovery GWAS.…”
Section: Resultsmentioning
confidence: 99%